EFFECTS OF LONG-TERM CONTINUOUS POSITIVE AIRWAY PRESSURE THERAPY (CPAP) ON EPICARDIAL FAT THICKNESS AND ARTERIAL STIFFNESS IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA AND HYPERTENSION - M. V. Gorbunova; S. L. Babak; A. G. Malyavin (Архивъ внутренней медицины, 2019)
Background: obstructive sleep apnea (OSA) is associated with high prevalence of arterial hypertension (AH), obesity, violation of carbohydrate metabolism and dyslipidemia. However, the effects of CPAP therapy to improve epicardial fat thickness of the OSA patient with AH the are poorly understood and poorly studied.Study objective: the aim of the study was to investigate 12-month effects of CPAP therapy with auto-adaptation to inhalation and exhalation of the OSA patient with AH and metabolic disorders (A-Flex therapy) on epicardial fat thickness (EFT).Methods: to the prospective single-center study were included 310 patients with OSA and AH (273 male, 45,3 ± 10,4 yr.) with apnea-hypopnea index (AHI) >5 events /hour. The night polygraphy study (PG) was performed to calculate AHI, oxygen desaturation index (ODI), mean nocturnal saturation (SpO 2 ) by the rules of American Academy of Sleep Medicine (AASM). The calculation of the epicardial fat thickness (EFT), the size and volume of the heart cavities, left ventricular mass index (LVMI) were performed by two-dimensional echocardiography. Endothelial functionof blood vessels determined by finger test was measured according to peripheral arterial tone (PAT). The reactive hyperemia index (RHI) and augmentation index (AI) was calculated. Optimal level of A-Flex therapy was adjusted at home. AHI, the level of air leakage, average pressure and compliance to CPAP treatment were established in accordance with international requirements.Results: after 3 months of A-Flex therapy we found a significant decrease of HOMA-IR -1,09 (95% Cl from -1,74 to -0,96; P=0,021), decrease AI -10.8% (95% Cl from -13,70 to -4.6; P=0,001), decrease EFT -1,26 mm (95% Cl from -2,2 to -0,95; P=0,001) in mild OSA patients. After 6 months of A-Flex therapy we found a significant decrease of HOMAIR -2,81 (95% Cl from -3,74 to -1,46; P=0,001), decrease AI -15.6 % (95% Cl from -17,23 to -11,75; P=0,001), decrease EFT -2,15mm (95% Cl from -3,2 to -1,5; P=0,001) in moderate OSA patients. After 12 months of A-Flex therapy we found a significant decrease of HOMA-IR -4,22 (95% Cl from -5,36 to -2,35; P=0,001), decrease AI -21,05 % (95% Cl from -26,5 to -17,4; P=0,001), decrease EFT -4,0 mm (95% Cl from-5,8 to -2,7; P=0,001) in severe OSA patients.Conclusions: The 12-month A-Flex therapy in moderate and severe OSA patients with AH has a significant therapeutic effect of stabilization systolic and diastolic blood pressure, level of blood lipids and epicardial fat thickness, level of endothelial dysfunction. The 12-month A-Flex therapy has to able to reduce the risks of cardiovascular events in moderate and severe OSA patients with acute metabolic manifestations.